2020
DOI: 10.1007/s42452-020-3182-5
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Fe3O4/MnO2 core–shell nano-composite for removal of heavy metals from wastewater

Abstract: Feasible reutilization of sorbents was crucial to the waste water treatment process cost-effective and environmental friendly. Magnetic Fe 3 O 4 /MnO 2 composites as sorbents were recycle utilized to remove heavy metals ions [Pb(II), Cu(II), Cd(II) and Zn(II)] from industrial wastewater. In this paper, The Fe 3 O 4 /MnO 2 composites structure and interface adsorption mechanism were investigated by chemical affinity, Zero potentials combining with XRD, FTIR and TEM. The adsorption, desorption and recycle experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 31 publications
2
7
0
1
Order By: Relevance
“…3 ). The same conclusion was reported by Li et al 42 for the adsorption of Zn 2+ , Cu 2+ , Cd 2+ , and Pb 2+ onto Fe 3 O 4 /MnO 2 nano-composites. On the other hand, the adsorbent dosage is particularly at the heart of applying any economic study of adsorbent per unit of wastewater to be treated.…”
Section: Adsorption Process and The Affecting Factorsupporting
confidence: 88%
See 2 more Smart Citations
“…3 ). The same conclusion was reported by Li et al 42 for the adsorption of Zn 2+ , Cu 2+ , Cd 2+ , and Pb 2+ onto Fe 3 O 4 /MnO 2 nano-composites. On the other hand, the adsorbent dosage is particularly at the heart of applying any economic study of adsorbent per unit of wastewater to be treated.…”
Section: Adsorption Process and The Affecting Factorsupporting
confidence: 88%
“…Accordingly, this could increase the efficiency of removing dyes and reduce the concentrations of other undesirable contaminants like heavy metals. 42 Baby et al 43 reported that adsorption of Cr 6+ , Pb 2+ , Cd 2+ , and Zn 2+ onto palm kernel shell adsorbent was increased with an increase in adsorbent dosage ( Fig. 3 ).…”
Section: Adsorption Process and The Affecting Factormentioning
confidence: 98%
See 1 more Smart Citation
“…The peak at 1646 cm −1 is due to stretching vibration from a combination of the Mn−O and −OH groups. 31 Figure 6b is the IR spectrum of the AX, in which a strong band at 3244 cm −1 was due to stretching of the −OH group of alginate. The appearance of strong bands at 1587 and 1416 cm −1 corresponds to asymmetric and symmetric stretching of the −COO (carboxyl) group of alginate, while the peak at 1025 cm −1 is due to stretching of the C−O−C bond.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Figure a shows the IR spectrum of mMO nanoparticles in which the peak at 3321 cm –1 is the characteristic stretching vibration peak of Fe–OH. The peak at 1646 cm –1 is due to stretching vibration from a combination of the Mn–O and −OH groups Figure b is the IR spectrum of the AX, in which a strong band at 3244 cm –1 was due to stretching of the −OH group of alginate.…”
Section: Resultsmentioning
confidence: 99%